Synthesis of Zeolite from Sugar Cane as Detergent Builder: Variation of Si/Al Ratio and Hydrothermal TimeSynthesis of Zeolite from Sugar Cane as Detergent Builder: Variation of Si/Al Ratio and Hydrothermal Time - Arnelli Arnelli; Noor Afifah; Narita Rizki; Tri Windarti; Yayuk Astuti (Jurnal Kimia Sains dan Aplikasi, 2018)
Synthesis of zeolite from bagasse with variation of Si / Al ratio (1,2,1,4,1,6 and 1,8) with ZS1-ZS5 code and hydrothermal time (160, 190, 250, 340, and 460 minutes) with sample code ZSa - ZSe has been conducted. The synthesized zeolite was then applied to the detergent builder. The detergent builder of synthetic zeolite was used as a substitute for sodium tripolyphosphate, which is not environmentally friendly as it can lead to eutrophication. One of the detergent builder functions is to improve the washing efficiency of the surfactant by inactivating water-absorbing minerals (Ca2+ and Mg2+ ions) which may further deter the detergency process. Zeolites were synthesized using a sol-gel method followed by a hydrothermal process. The material used in this synthesis is Na2SiO3 (aq) (derived from bagasse) mixed with NaAl(OH)4 (aq), then stirred to form a white gel and continued by heating using autoclave at 100°C. The results obtained are zeolite-A and zeolt-X for variation of Si/Al ratio and hydrothermal time variation, with CEC value and detergency proportional to Si/Al ratio and hydrothermal time.